2010
DOI: 10.1161/circresaha.110.218487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Notch1-Dependent Cardiomyogenesis Leads to a Dilated Myopathy in the Neonatal Heart

Abstract: Rationale: Physiological hypertrophy in the developing heart has been considered the product of an increase in volume of preexisting fetal cardiomyocytes in the absence of myocyte formation. Objective: In this study, we tested whether the mouse heart at birth has a pool of cardiac stem cells (CSCs) that differentiate into myocytes contributing to the postnatal expansion of the parenchymal cell compartment. Methods and Results: We have found that the newborn heart contains a population of c-kit-positive CSCs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 40 publications
(52 reference statements)
2
65
0
1
Order By: Relevance
“…Together, these results show that Notch-1 signaling is down-regulated in myocardium in early-stage DCM. Our findings are consistent with previous reports of development of DCM in vitro and in newborn mice treated with an inhibitor of Notch-1-dependent signaling (36), or more pronounced cardiac dysfunction, fibrosis, and apoptosis in adult hearts from an agonist-induced hypertrophy model or Notch-1 cardiac-specific null mice (37). Similarly, transgenic mice overexpressing the Notch ligand JAGGED1 were protected from pressure overloadinduced cardiac hypertrophy (38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Together, these results show that Notch-1 signaling is down-regulated in myocardium in early-stage DCM. Our findings are consistent with previous reports of development of DCM in vitro and in newborn mice treated with an inhibitor of Notch-1-dependent signaling (36), or more pronounced cardiac dysfunction, fibrosis, and apoptosis in adult hearts from an agonist-induced hypertrophy model or Notch-1 cardiac-specific null mice (37). Similarly, transgenic mice overexpressing the Notch ligand JAGGED1 were protected from pressure overloadinduced cardiac hypertrophy (38).…”
Section: Discussionsupporting
confidence: 93%
“…Dilated cardiomyopathy, left ventricular noncompaction, cardiac development (36,40) VIP signaling map3k1(s915), ppp3cb(s469), plcg1(s1263), nfatc2(s136), prkar2b(s112), prkacb, prkar2a, prkar1a, nfkb1, ppp3ca…”
Section: Pathwaymentioning
confidence: 99%
“…When Notch signaling was blocked in newborn mice by the administration of DAPT, the mortality rate tended to increase. After DAPT cessation, cardiac function was largely restored [52] . Furthermore, a previous study showed that activation of Notch1 signaling in H9c2 cardiomyoblasts contributed to the cardioprotection provided by ischemic preconditioning and postconditioning [53] .…”
Section: Discussionmentioning
confidence: 99%
“…155 Accumulated evidence suggests that resident CSC recruitment and differentiation are mediated by Notch-mediated induction of reparative mechanisms in the damaged heart. [155][156][157][158] Urbanek et al 159 showed that pharmacological inhibition of Notch reduces the number of cycling c-kit+ CSCs and compromises their cardiac commitment. Moreover, inhibition of Notch signaling leads to severe dilated cardiomyopathy in newborn mice secondary to the reduced differentiation rate of cardiac progenitor cells.…”
Section: Differentiationmentioning
confidence: 99%
“…Moreover, inhibition of Notch signaling leads to severe dilated cardiomyopathy in newborn mice secondary to the reduced differentiation rate of cardiac progenitor cells. 159 …”
Section: Differentiationmentioning
confidence: 99%